Pylephlebitis with Bacteremia from a Rare Bacterium: A Case Report of Septic Mesenteric-Portal Thrombophlebitis Associated with Acute Diverticulitis - Moreira, Paula Heroso; Costa, Giovana Rezende Fernandes Costa; Terasoto, Lucas; Eli, Gabriel da Silva; Faro, Barbara Loeser; Parreira, Pedro Henrique Garcia; Parreira, Pedro Henrique Garcia; Nasr, Adonis (Brazilian Journal of Case Reports, 2024)
Pylephlebitis, defined as septic thrombophlebitis of the portal vein, is a rare complication of intra-abdominal infections, particularly appendicitis and diverticulitis. Prompt diagnosis through laboratory tests and imaging, and the early institution of antibiotic therapy, with or without anticoagulation, considerably improve the prognosis. The authors present an atypical case of pylephlebitis associated with uncomplicated acute diverticulitis, with the isolation of a rare bacterium in peripheral blood, Sutterella wadsworthensis.